Irregular Wave Forces on a Large Vertical Circular Cylinder. (September 2016) - Aggarwal, Ankit; Chella, Mayilvahanan Alagan; Kamath, Arun; Bihs, Hans; Arntsen, Øivind Asgeir
Abstract: Substructures of offshore wind turbines are exposed to irregular sea states that are generally defined using wave spectra. The waves undergo transformations due to non-linear wave-wave interactions and due to interaction with the structures they are incident on. In the present study, simulations of regular and irregular wave interaction with a vertical cylinder are carried out using the open- source Computational Fluid Dynamics (CFD) model REEF3D. The model solves the Reynolds Averaged Navier-Stokes (RANS) equations over the entire domain and provides detailed information regarding the wave hydrodynamics including fluid pressure, velocities and the free surface. The non-linear wave-wave, wave-structure interactions and the turbulence in the flow are accounted for in the solution of the RANS equations. In this way, detailed flow features around the cylinders can be visualised and analysed. The numerical model is verified with the analytical equations for the loads on a cylinder under regular waves. Further, simulations are carried out for irregular waves generated using the JONSWAP wave spectrum and the wave force spectrum is calculated. The wave spectrum for the different wave gauges around the cylinder are compared. The free surface features around the cylinder are visualised and correlated to the wave forces on the cylinder. It is observed that the regular waves with higher steepness show a clear diffraction pattern around the cylinder. For the irregular waves, the diffraction pattern is less developed and irregular.